2018
DOI: 10.5935/0946-5448.20180015
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ESS on Olfactory Threshold of Patients with CRS without Nasal Polyps

Abstract: Objectives: Chronic rhinosinusitis (CRS) is characterized by a long-time inflammatory disease of nasal and sinus mucosa. Olfactory dysfunction is common among CRS patients with a prevalence ranging from 48% to 83%. We aimed to assess the effect of ESS on olfactory function of patients with chronic rhinosinusitis without nasal polyps.Method: This randomized clinical trial was conducted on 30 patients with chronic rhinosinusitis without nasal polyps. Patients were randomly allocated to two intervention and contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 17 publications
(20 reference statements)
0
8
0
Order By: Relevance
“…In a prospective, multi‐center study, CRS patients treated with ESS had better olfactory function than who were treated with medication 130 . in contrast, some studies revealed that there were no significant differences in olfactory function between ESS and standard medical therapy groups 102,131 . These differences in outcome may be due in part to the heterogeneity in patients involved and to methods used for assessment.…”
Section: Olfaction Indicates the Degree Of Inflammation And May Be A mentioning
confidence: 96%
See 2 more Smart Citations
“…In a prospective, multi‐center study, CRS patients treated with ESS had better olfactory function than who were treated with medication 130 . in contrast, some studies revealed that there were no significant differences in olfactory function between ESS and standard medical therapy groups 102,131 . These differences in outcome may be due in part to the heterogeneity in patients involved and to methods used for assessment.…”
Section: Olfaction Indicates the Degree Of Inflammation And May Be A mentioning
confidence: 96%
“…However, as discussed above, subjective and objective testing have been shown to correlate poorly—with subjective ratings being confounded by numerous factors including nasal airflow and the patients expectations 27 . Yousefi et al's study revealed there are not significantly improvement in olfactory threshold among 16 CRSsNP patients after 3 months topical corticosteroids and nasal irrigation of normal saline ( P = .311 for men and P = .139 for women) 102 …”
Section: Olfaction Indicates the Degree Of Inflammation And May Be A mentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that nasal saline irrigation was ineffective in many studies conducted on nasal saline irrigation in patients with chronic rhino-sinusitis [ 23 , 24 ]. In a meta-analysis; however, it was found that hypertonic saline irrigation was more effective in the treatment of chronic rhino-sinusitis compared to isotonic irrigation [ 25 , 26 ]. In our study, it was found that there were no significant increases in self-rating olfactory scores in patients who did irrigation with nasal saline compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Nasal polyp (NP) is benign growths of the mucosa. [14] It is manifested that this disorder includes nasal obstruction, nasal discharge, postnasal drip, and loss of smell. [57] If such disorder cannot treat fairly well, it can cause recurrent nature of NP and can significant impact heath-related quality of life.…”
Section: Introductionmentioning
confidence: 99%